The Proposed Development of Prototype with Secret Messages Model in Whatsapp Chat - Hamdani Hamdani; Heru Ismanto; Agus Qomaruddin Munir; Budi Rahmani; Andri Syafrianto; Didit Suprihanto; Anindita Septiarini (International Journal of Electrical and Computer Engineering (IJECE), 2018)
Development of prototype at data security through secret messages is needed for disguising the messages sent in smartphone chatting application, WhatsApp (WA) Chat. We propose a model to disguise a plaintext message which is first encrypted by cryptosystem to change the plaintext message to ciphertext. Plaintext or plainimage entering the smartphone system is changed into encrypted text; receiver then can read the message by using similar key with the sender. The weakness of this proposal is the message random system is not planted directly in the chatting application; therefore message removing process from cryptosystem to WA application is still needed. The strength of using this model is the messages sent will not be easily re-encrypted by hacker and can be used at client computing section.